Odpowiedź :
1. x = -2
-4(5+3·-2) = -4 · -1 = 4
2. p:5
[tex]\frac{x+x^{3} }{2}[/tex]
[tex]\frac{2}{3}n[/tex]
3. II
4. B
Odpowiedź:
1.
-4(5 + 3x) = -20 - 12x = -20 + 24 = 4
x = -2
odp.A.
2.
a)
p/5
b)
(x + x³)/2 = 1/2x + 1/2x³
c)
x = 2/5 * n
3.
I. -1/3(x - 3y + 6z - 9) = -1/3x + y + 2z -3 zle
= -1/3x + y - 2z + 3
II (3x + y) + (x + 2y) - (3x - y) = x + 4y dobrze
= 3x + y + x + 2y - 3x + y = x + 4x
III. 7x - y + x - 4y = 8x - 3y zle
= 8x - 5y
4.
konewka - 8l
wiadro - 10l
i * 8l + j * 10l + 1/2 * 8l = 8i + 10j + 1/2
odp. D.
Szczegółowe wyjaśnienie: